La advertencia de los autómatas de Eduardo L. Holmberg: el simulacro artificial en Argentina - Menczel, Gabriella (Verbum – Analecta Neolatina, 2014)
Eduardo L. Holmberg was a versatile Argentinean author in the 19th century, particularly interested in the natural sciences, who introduced the genre of science fiction in Argentinean literature. This paper focuses on his short story “Horacio Kalibang o los autómatas” (1879) from the perspectives of identity inversions, creation of mechanic simulacrums of human beings as a projection of a hyperreality (Baudrillard). The artificial simulacrum is produced within the frames of dynamic games such as identity vs. alterity, or in Paul Ricoeur’s terms, identity (mêmeté) vs. ipseity (ipséité). This study presents the narrative techniques of creating a sinister reality, and the way of converting the identities into victims manipulated by an unconceivable superior power.